INTERACTIVE GRID COMPUTING: ADAPTING HIGH LEVEL ARCHITECTURE-BASED APPLICATIONS TO THE GRID - KATARZYNA RYCERZ; MARIAN BUBAK; MACIEJ MALAWSKI; PETER SLOOT (TASK Quarterly, 2004)
In this paper we present the design of a Grid HLA Management System (GHMS) supporting execution of High Level Architecture-based interactive applications in a Grid environment, while at the same time allowing for running HLA legacy codes to preserve backward compatibility with the HLA standard. In particular, we describe the following system components: an HLA-Speaking Service for multiple federates that interface the HLA application to the system, a Monitoring Service integrated with the OCM-G monitoring system and HLA-based Benchmark Services informing the Broker Service of what can be expected from the application’s behavior.